General Knowledge and Attitudes Toward Organ Donation in a Sample of Mexican Medical and Nursing Students - Ma. Luisa Marván (Revista Ciencias de la Salud, 2020)
Introduction: For many patients, organ transplantation is the only alternative available to them in order to achieve extended survival with a good quality of life. However, there is a significant shortage of organs available for transplantation and Mexico has one of the lowest organ donation rates. In many cases, physicians and nurses retain contact with potential donors’ relatives who are key persons in facilitating the posthumous organ donation process. The objective of this study was to explore what knowledge and attitudes Mexican medical and nursing students have toward organ donation. Materials and methods: Three hundred eighty-four students completed two questionnaires, one about organ donation knowledge and the other about attitudes toward organ donation. Results: Participants, especially nursing students, showed an inadequate level of knowledge about organ donation. Many of them falsely believe that it is possible to recover from brain death. Most students also falsely believe that there is an age limitation for organ donation, and that prevailing religions in Mexico are opposed to organ donation. There was a negative correlation between knowledge of and unfavorable attitudes toward organ donation. Conclusions: It may be necessary to review current school curriculum to ensure that future health professionals are appropriately educated about organ donation and can promote donation to help reduce the shortage of organs.